Heyzine Flipbook Based E-Book for Enhancing Students’ Critical Thinking Skills of Junior high school: A Study Development - Sriyanti Sriyanti; Eges Triwahyuni; I Wayan Wesa Atmaja (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to analyze the effectiveness of a Heyzine Flipbook-based e-book in improving students’ critical thinking skills in Pancasila Education learning. The research employed a quasi-experimental design using a nonequivalent control group design. The participants consisted of two classes: an experimental class that used the Heyzine Flipbook-based e-book and a control class that used conventional textbook media. The results showed that the mean posttest score of the experimental class (83) was higher than that of the control class (60). The average N-Gain score of the experimental class was 0.66 (moderate category), while the control class obtained 0.27 (low category). The independent sample t-test indicated a significance value of p < 0.05, demonstrating a statistically significant difference between the two groups. Furthermore, the effect size was categorized as large, indicating that the Heyzine Flipbook-based e-book had a strong impact on enhancing students’ critical thinking skills. Therefore, the Heyzine Flipbook-based e-book was effective as an alternative digital learning medium to support the development of students’ critical thinking skills.